What an English Teacher Knows: Teaching in the Post-truth Era. Issue 1 (2nd January 2021) - Wescott, Stephanie
ABSTRACT: Post-truthism entered mainstream consciousness after being named Oxford Dictionary's word of the year in 2016, denoting a turn in the Western relationship with truth as a certain and indisputable object. Simultaneously, and paradoxically, rising distrust around teachers' professional judgement and a desire for certainty in practice saw the proliferation of 'evidence-informed' approaches and the impetus for teachers to use data to inform their decision-making. This paper places recent changes to practice and policy in the post-truth context, suggesting that the trends of evidence-based practice and datafication can be understood within this socio-political phenomenon. It is suggested that in a moment looking for assurance and certainty, post-truth rationalities seep into education, eroding the agentic properties of English teacher knowledge in favour of mechanisms promising certitude and reliability and sacrificing subjectivity and nuance.